PRODUKTIFITAS SAPI PERANAKAN ONGOLE PADA PEMELIHARAAN INTENSIF - Nena Hilmia; Dudi Dudi; Primiani Edianingsih; Muhammad Syahid Panji Pangestu; Dikdik Nurulhadi (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2024)
Beef cattle productivity can be evaluated based on the Average  Daily Gain (ADG), feed consumption, and Feed Conversion ratio (FCR). This research aims to assess the productivity of Ongole crossbreed cattle (PO) that are reared intensively. A total of fifteen cattle were used in this study, aged 2-2.5 years. Cattle were reared intensively in individual pens for 61 days, equipped with feed and water. The feed was given a mixture of concentrate and forage in a ratio of 75: 25,  water was given ad libitum. The total dry matter requirement was calculated based on 3% of body weight. The parameters observed were Average Daily Gain (ADG), feed consumption, and Feed Conversion Ratio (FCR). The data were analyzed by descriptive analysis. The study indicated that ADG was 0.625 ± 0.136 kg, the average of feed consumption was 7.35 ± 1.67 kg and the average of FCR was 12.582 ± 5.149.